Cross-cultural examination of the Big Five Personality Trait Short Questionnaire: Measurement invariance testing and associations with mental health. - Laura Mezquita; Adrian J Bravo; Julien Morizot; Angelina Pilatti; Matthew R Pearson; Manuel I Ibáñez; Generós Ortet; Cross-Cultural Addictions Study Team (PLoS ONE)
The present study examined the measurement invariance of the Big Five Personality Trait Short Questionnaire (BFPTSQ) across language (Spanish and English), Spanish-speaking country of origin (Argentina and Spain) and gender groups (female and male). Evidence of criterion-related validity was examined via associations (i.e., correlations) between the BFPTSQ domains and a wide variety of mental health outcomes. College students (n = 2158) from the USA (n = 1117 [63.21% female]), Argentina (n = 353 [65.72% female]) and Spain (n = 688 [66.86% female]) completed an online survey. Of the tested models, an Exploratory Structural Equation Model (ESEM) fit the data best. Multigroup ESEM and ESEM-within-CFA generally supported the measurement invariance of the questionnaire across groups. Internalizing symptomatology, rumination and low happiness were related mainly to low emotional stability across countries, while low agreeableness and low conscientiousness were related chiefly to externalizing symptomology (i.e., antisocial behavior and drug outcomes). Some correlational differences arose across countries and are discussed. Our findings generally support the BFPTSQ as an adequate measure to assess the Big Five personality domains in Spanish- and English-speaking young adults.